2019
DOI: 10.1073/pnas.1912356116
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas vaginalis extracellular vesicles are internalized by host cells using proteoglycans and caveolin-dependent endocytosis

Abstract: Trichomonas vaginalis, a human-infective parasite, causes the most prevalent nonviral sexually transmitted infection worldwide. This pathogen secretes extracellular vesicles (EVs) that mediate its interaction with host cells. Here, we have developed assays to study the interface between parasite EVs and mammalian host cells and to quantify EV internalization by mammalian cells. We show that T. vaginalis EVs interact with glycosaminoglycans on the surface of host cells and specifically bind to heparan sulfate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 60 publications
4
59
0
Order By: Relevance
“…A classic example of EV contribution to intercellular communication without deliver their content resides in those vesicles that harbor MHC molecules on their surface, thus activating T cell receptors on T cells ( Raposo et al, 1996 ; Martin et al, 2014 ). Concerning the delivery of EV content, EVs can be taken up by target cells through several mechanisms, including clathrin-mediated endocytosis, caveolin-dependent endocytosis, macropinocytosis, phagocytosis, lipid rafts, and cell surface membrane fusion ( Feng et al, 2010 ; Montecalvo et al, 2012 ; Svensson et al, 2013 ; Tian et al, 2014 ; Costa Verdera et al, 2017 ; Rai and Johnson, 2019 ). Although numerous receptors/ligands are implicated into EV uptake including tetraspanins, integrins, immunoglobulins, lectins, and proteoglycans ( Morelli et al, 2004 ; Hao et al, 2007 ; Barrès et al, 2010 ; Christianson et al, 2013 ), to date it is still debated whether EV uptake is a cell-type specific process or not.…”
Section: Characterization Of Evsmentioning
confidence: 99%
“…A classic example of EV contribution to intercellular communication without deliver their content resides in those vesicles that harbor MHC molecules on their surface, thus activating T cell receptors on T cells ( Raposo et al, 1996 ; Martin et al, 2014 ). Concerning the delivery of EV content, EVs can be taken up by target cells through several mechanisms, including clathrin-mediated endocytosis, caveolin-dependent endocytosis, macropinocytosis, phagocytosis, lipid rafts, and cell surface membrane fusion ( Feng et al, 2010 ; Montecalvo et al, 2012 ; Svensson et al, 2013 ; Tian et al, 2014 ; Costa Verdera et al, 2017 ; Rai and Johnson, 2019 ). Although numerous receptors/ligands are implicated into EV uptake including tetraspanins, integrins, immunoglobulins, lectins, and proteoglycans ( Morelli et al, 2004 ; Hao et al, 2007 ; Barrès et al, 2010 ; Christianson et al, 2013 ), to date it is still debated whether EV uptake is a cell-type specific process or not.…”
Section: Characterization Of Evsmentioning
confidence: 99%
“…Glycosaminoglycans (GAGs), heparan sulfate proteoglycan (HSPGs) chains, and other unidentified host cell surface components mediated T. vaginalis EV uptake because the loss of host cell surface GAGs and HSPGs reportedly reduced, but did not completely block the uptake of T. vaginalis EVs (Rai and Johnson, 2019 ). Furthermore, the treatment of the host cells with a specific inhibitor of lipid raft-mediated endocytosis reduced T. vaginalis EV uptake to a considerable point.…”
Section: Mechanisms Of Ppevs Internalizationmentioning
confidence: 99%
“…Furthermore, the treatment of the host cells with a specific inhibitor of lipid raft-mediated endocytosis reduced T. vaginalis EV uptake to a considerable point. To this end, the cellular uptake of T. vaginalis EVs required cholesterol in addition to caveolin-dependent, lipid raft proteoglycan-mediated endocytosis (Rai and Johnson, 2019 ). Incidentally, Garcia-Silva et al ( 2014 ) reported T. cruzi vesicles coated with clathrin from early endocytosis and the trans-Golgi membrane network.…”
Section: Mechanisms Of Ppevs Internalizationmentioning
confidence: 99%
“…The major neutrophil-recruitment factor is likely to be the cytokine IL-8, as it is released rapidly and abundantly from multiple cellular sources and facilitates both extravasation and homing to microenvironments within tissues. Interestingly, Tv was recently shown to produce and secrete exosomes, small extracellular vesicles that contain RNA and protein and can be uptaken by host cells [ 46 , 106 ]. In addition to increasing host cell susceptibility to parasite attachment, Tv exosomes also seem to have the ability to suppress neutrophil recruitment, as host epithelial cells that were pretreated with Tv exosomes showed a reduction in IL-8 response upon subsequent parasite encounter [ 46 ].…”
Section: Tv Evasion From Neutrophilsmentioning
confidence: 99%